Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Cerita Sistem Persamaan Linear Dua Variabel Ditinjau Dari Taksonomi Solo Pada Siswa Kelas X SMA Muhammadiyah 1 Karanganyar Tahun 2016/2017 - Nugroho, Fajar Ahmad; , Dra. Sri Sutarni, M.Pd (2017)
The research aimed to describe the mistakes of the student in resolving story question of linear equation system of two variable in terms of five levels SOLO taxonomy and the factors that cause errors stretcher. Type of the research was descriptive. The subject were students of class X3 Senior High School of Muhammadiyah 1 Karanganyar contains 40 students. Technique of collecting data in this research using test, interview, and documentation. Data validity was used triangulation of sources and technique. Triangulation of source is the test result of the student and interview result while triangulation of technique using test, interview, and documentation.Technique of analysing data conducted by stages data reduction, data presntation, and conclusing or verification. The result found level precentage of prestructural 18,05%, unistructural level 30,73%, multistruktural level 24,63%, relational level 15,61%, and extended abstract level 10,98%. The result indicate student errors at the level of unistruktural is most widelythan another level. Factor leading to incorrect unistruktural level is the lack of student in understanding information of the question, the lack of rigor, and student are unable to translate into a sentence in mathematics or mathematical models.